2004
DOI: 10.1007/s00442-004-1511-9
|View full text |Cite
|
Sign up to set email alerts
|

Density-dependent effects of multiple predators sharing a common prey in an endophytic habitat

Abstract: Multiple predator species feeding on a common prey can lead to higher or lower predation than would be expected by simply combining their individual effects. Such emergent multiple predator effects may be especially prevalent if predators share feeding habitat. Despite the prevalence of endophagous insects, no studies have examined how multiple predators sharing an endophytic habitat affect prey or predator reproduction. We investigated density-dependent predation of Thanasimus dubius (Coleoptera: Cleridae) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Responses by prey exposed simultaneously to multiple predators are often predicted poorly by the sum of pair-wise predator-prey interactions (e.g., Sih et al 1998;Relyea 2003;Aukema et al 2004;Teplitsky et al 2004), implying that the results of experiments utilizing single-predator environments may not always be applicable to natural situations. Here, however, we demonstrate that the independent and opposite eVects of two predators on prey phenotype can dampen one another: the directional outcomes of pair-wise interactions between R. clamitans embryos and two stage-speciWc predators were not observed when embryos were exposed to cues from both predators simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Responses by prey exposed simultaneously to multiple predators are often predicted poorly by the sum of pair-wise predator-prey interactions (e.g., Sih et al 1998;Relyea 2003;Aukema et al 2004;Teplitsky et al 2004), implying that the results of experiments utilizing single-predator environments may not always be applicable to natural situations. Here, however, we demonstrate that the independent and opposite eVects of two predators on prey phenotype can dampen one another: the directional outcomes of pair-wise interactions between R. clamitans embryos and two stage-speciWc predators were not observed when embryos were exposed to cues from both predators simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Like T. dubius , P. cylindrica larvae feed on I. pini and other species present. A previous laboratory study found some evidence of intraguild predation of T. dubius larvae on P. cylindrica pupae at high predator densities, but this experiment was conducted at a single, moderate I. pini density (Aukema et al ., 2004a).…”
Section: Methodsmentioning
confidence: 99%
“…These densities reflect natural colonisation patterns of 0–2.5 males per dm 2 (Schenk & Benjamin, 1969; Poland & Borden, 1994; Robins & Reid, 1997). Two females per male were added overall, with the sex ratio being 3:2 on day 1 and 1:6 on day 2, to mimic natural arrival patterns (Aukema et al ., 2004a). There were 10 logs per series, with two logs each of four and eight males, and one log each of 12, 16, 20, 24, 28, and 32 males.…”
Section: Methodsmentioning
confidence: 99%
“…1). The positioning of the preferences of I. pini midway between the preferences of the two major predators may arise from equal and opposing pressures they exert, i.e., they occur in approximately equal numbers (Table 1), show equivalent numerical relationships with I. pini populations in nature , and have equivalent and noninteracting per-predator eVects on I. pini reproduction within hosts (Aukema et al 2004). Incorporating a synergist into their pheromone plume gives I. pini further opportunity to communicate with only moderate or with no additional eavesdropping by predators.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of Weld populations indicate strong density-dependent relationships , and laboratory assays indicate strong eVects on beetle survival and reproduction . Further, each predator species exerts equivalent eVects on beetle reproduction, and there are no nonadditive interference or augmentation eVects (Aukema et al 2004). These predators can be considered habitat generalists, in that they develop exclusively within trees killed by bark beetles, but feed on several species of primary colonizers and secondary opportunists in such trees .…”
Section: Description Of Model Systemmentioning
confidence: 99%